2021
DOI: 10.1007/s12602-021-09767-7
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model)

Abstract: A strain of Alcaligenes faecalis A12C (A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis. We used 30 male rats, randomly divided into 6 groups (n = 5): three groups (HA7, HA15, HA30) received A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
3
5
0
Order By: Relevance
“…Recently, our research group has shown the potential probiotic effect of this strain in mammals. Administration of A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days was associated in this study with a lesser spread of infection, obtaining promising clinical, microbiological, biochemical and histopathological results in a rat model of peritonitis produced by E. coli [20]. These ndings, together with the scarcity of studies focused on the probiotic properties of this strain [56], set us the objective of evaluating whether the administration of A. faecalis A12C would generate a preventive effect against the damage caused by sepsis, as well as to identify the possible immunomodulatory mechanisms of action in an experimental model in rats.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Recently, our research group has shown the potential probiotic effect of this strain in mammals. Administration of A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days was associated in this study with a lesser spread of infection, obtaining promising clinical, microbiological, biochemical and histopathological results in a rat model of peritonitis produced by E. coli [20]. These ndings, together with the scarcity of studies focused on the probiotic properties of this strain [56], set us the objective of evaluating whether the administration of A. faecalis A12C would generate a preventive effect against the damage caused by sepsis, as well as to identify the possible immunomodulatory mechanisms of action in an experimental model in rats.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the survival rate of healthy animals, that were administered the strain, was not affected. Regarding the clinical signs due to sepsis, and although there are authors who nd clinical signs similar to ours [20,34], but there are not papers with quantitative studies of these variables using the rat CLP model in probiotics e cacy studies.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…A. faecalis bacteria is usually considered non-pathogenic and has even been proposed as a potential probiotic [ 7 ]. Opportunistic infections due to A. feacalis do occur in humans [ 8 ]; however, previous cases of A. faecalis osteomyelitis have only been rarely reported. Skin and soft tissue infections of A. faecalis , including infections associated with diabetic foot ulcers, have been previously described; however, to the authors’ knowledge, only three other cases of A. faecalis osteomyelitis have been reported, all three in patients with diabetic foot ulcers [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%